OUR EXPERIENCE IN TREATING PATIENTS WITH RESISTANT TRIGEMINAL NEURALGIA BY BALLOON MICROCOMPRESSIONGASSER'SNODE - Потапов, О. І.; Мартин, А. Ю.; Гринів, Ю. В.; Ткачук, Ю. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Analysis of results of treatment of trigeminal neuralgia for by balloon mikrokompresion Gasser node in early and late periods after surgery showed high efficiency of this method in the vast majority of operated patients. These data suggest the feasibility of a wider implementation of this operation in neurosurgical departments.